Republic of Armenia : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2019)
This paper presents Fiscal Transparency Evaluation (FTE) for Armenia. This report provides 10 recommendations aimed at further enhancing fiscal transparency in the areas prioritized. Fiscal forecasts and budgets have become more forward looking and policy oriented, with the introduction of a medium-term expenditure framework (MTEF), improved fiscal objectives, and a performance budgeting system. The report presents the assessment of fiscal transparency practices against the IMF's Fiscal Transparency Code (FTC). Armenia's fiscal transparency practices have strengths and weaknesses in all areas of FTC: fiscal reporting, fiscal forecasting and budgeting, and fiscal risk disclosure and management. The fiscal transparency evaluation also estimates Armenia's public sector financial position, in order to provide a more comprehensive view of public finances. Expanding the institutional coverage of Armenia's fiscal reports to the entire public sector would increase the deficit by 1.3 percent of gross domestic product and would have a material impact on revenue and expenditure.